Education and social justice in a digital age - Sutherland, Rosamund 1947-2019 (The Policy Press, 2014)
This book proposes an approach to changing the educational system in order to redress inequalities in society, whilst at the same time acknowledging the potential transformative role of digital technologies
Title from publisher's bibliographic system (viewed on 04 Feb 2022)
Keywords: Social justice / Study and teaching; Education / Curricula